The effect of Sn concentration on oxide texture and microstructure formation in zirconium alloys. (15th October 2015) - Garner, Alistair; Hu, Jing; Harte, Allan; Frankel, Philipp; Grovenor, Chris; Lozano-Perez, Sergio; Preuss, Michael
Abstract: The development of oxide texture and microstructure formed on two zirconium alloys with differing Sn contents (Zr–1Nb–1Sn–0.1Fe, i.e. ZIRLO™ and Zr–1.0Nb–0.1Fe) has been investigated using transmission Kikuchi diffraction (TKD) in the scanning electron microscope (SEM) and automated crystal orientation mapping in the transmission electron microscope (TEM). Bulk texture measurements were also performed using electron backscatter diffraction (EBSD) in order to quantify and compare the oxide macrotexture development. The Sn-free alloy showed significantly improved corrosion performance by delay of the transition region and reduced levels of hydrogen pickup. The macroscopic texture and grain misorientation analysis of the oxide films showed that the improved corrosion performance and reduced hydrogen pick up can be correlated with increased oxide texture strength, the improved oxide grain alignment resulting in longer, more protective columnar grain growth. A lower tetragonal phase fraction is also observed in the Sn-free alloy. This results in less transformation to the stable monoclinic phase during oxide growth, which leads to reduced cracking and interconnected porosity and also to the formation of larger, well-aligned monoclinic grains. It is concluded that the Zr–1.0Nb–0.1Fe alloy is more resistant to hydrogen pickup due the formation of a denser oxide with a larger columnar grain structure.